2011
DOI: 10.1002/chem.201100120
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Plutonium(VI) at Variable Temperatures (283–343 K)

Abstract: The hydrolysis of Pu(VI) was studied at variable temperatures (283-343 K) by potentiometry, microcalorimetry, and spectrophotometry. Three hydrolysis reactions, mPuO(2)(2+) + nH(2)O=(PuO(2))(m)(OH)(n) (2m-n)( +) + nH(+)), in which (n,m)=(1,1), (2,2), and (5,3), were invoked to describe the potentiometric and calorimetric data. The equilibrium constants (*β(n,m)) were determined by potentiometry at 283, 298, 313, 328, and 343 K. As the temperature was increased from 283 to 343 K, *β(1,1), *β(2,2), and *β(5,3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
(35 reference statements)
0
17
0
1
Order By: Relevance
“…[37,38] The stock solutions of 237 Np VI and 242 Pu VI in perchloric acid were prepared using the method of HClO 4 fuming as described previously. [39] Absorption spectra were collected to confirm the oxidation states of Np VI and Pu VI in the stock solutions. The concentrations of Np VI and Pu VI were determined, respectively, by the absorbance at 1122 nm (e = 43 m À1 cm À1 for NpO 2 2 + ) [29] and 830.5 nm (e = 550 m À1 cm À1 for PuO 2 2 + ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37,38] The stock solutions of 237 Np VI and 242 Pu VI in perchloric acid were prepared using the method of HClO 4 fuming as described previously. [39] Absorption spectra were collected to confirm the oxidation states of Np VI and Pu VI in the stock solutions. The concentrations of Np VI and Pu VI were determined, respectively, by the absorbance at 1122 nm (e = 43 m À1 cm À1 for NpO 2 2 + ) [29] and 830.5 nm (e = 550 m À1 cm À1 for PuO 2 2 + ).…”
Section: Methodsmentioning
confidence: 99%
“…The stock solution of U VI in perchloric acid was prepared and standardized as described elsewhere 37. 38 The stock solutions of 237 Np VI and 242 Pu VI in perchloric acid were prepared using the method of HClO 4 fuming as described previously 39. Absorption spectra were collected to confirm the oxidation states of Np VI and Pu VI in the stock solutions.…”
Section: Methodsmentioning
confidence: 99%
“…This will also enhance Pu 4+ hydrolysis. Endothermic hydrolysis behavior of aqueous Pu and other actinide species has been reported in numerous studies (Altmaier et al, 2013;Rao et al, 2004;Rao et al, 2011;Runde et al, 2002). Dash (25 C) and solid lines (80 C) are fitted curves using 1 st order kinetic model.…”
Section: Sorption Kinetics In the Aqueous Pu(iv)-montmorillonite Systemmentioning
confidence: 94%
“…Thus, understanding Pu behavior at elevated temperatures is necessary. The paucity of thermodynamic and kinetic data limits the efficacy of current transport model predictions (Altmaier et al, 2013;Rao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[21], the average number of ligands is 3.3 only (R Pu-OH2 = 2.47 Å); Madic et al [22] found the five water molecules (R Pu-Oyl = 1.81 Å and R Pu-OH2 = 2.47 Å), and according to EXAFS measurements of Panak et al [23], the number of equatorial ligands was 3.8 (R Pu-Oyl = 1.82 Å, R Pu-OH2 = 2.48 Å). In DFT calculations of Hay et al [24], the obtained R Pu-Oyl distance (1.81 Å) 6+ complexes, though the existence of these species in aqueous solutions was experimentally confirmed [1][2][3][4][31][32][33][34][35]. To the best of our knowledge, only one work [25] Thus, in all previous simulations, the two approaches for constructing of Pu Z+ aqueous complexes were used: (1) the more or less constrained geometry optimization of the clusters composed of plutonium (or plytonyl) ion with the fixed first solvation shell and some constant number of water molecules modeling the second solvation shell; (2) MD modeling of periodic supercells based on pair-potentials with fitting parameters.…”
Section: +mentioning
confidence: 99%